The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1159/000292033
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Hysteroscopic Metroplasty on the Reproductive Outcome in a ‘T-Shaped’ Uterus

Abstract: Eight women (aged 27-43) with reproductive dysfunction who were diagnosed by hysterosalpingogram and hysteroscopy as having a ‘T-shaped’ uterus were operated on using fiberoptic hysteroscopic guidance; the uterine side walls were incised until a normal uterine cavity was achieved. The women’s gynecologic and obstetric records were compared before and after the operation. In all the 8 women the operation was without complications and resulted in a satisfactory uterine cavity. Before the operative procedure, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(40 citation statements)
references
References 7 publications
(11 reference statements)
5
33
1
1
Order By: Relevance
“…For T-shaped uterus, metroplasty was performed according to the description and technique of Katz et al [11] and the uterine side walls were incised until a normal uterine cavity was achieved.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For T-shaped uterus, metroplasty was performed according to the description and technique of Katz et al [11] and the uterine side walls were incised until a normal uterine cavity was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…In a series of 8 cases, Katz et al [11 ]in 1996 concluded that hysteroscopic metroplasty in women with a T-shaped uterus improves the reproductive outcome, and women with this anomaly who want to improve their reproductive function should be encouraged to undergo hysteroscopic metroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed a successful outcome of term deliveries in three out of six women with recurrent miscarriages, and no success in two women with primary infertility. In the same way, Katz et al 7 published a study concerning eight women with a 'T-shaped' uterus. The post-operative performance available for seven of the eight women showed four term pregnancies and one ectopic pregnancy in three women with secondary infertility.…”
Section: Discussionmentioning
confidence: 95%
“…Different methods and instruments for the hysteroscopic metroplasty have been used, including scissors 6 and a resectoscope with a monopolar hook 7,8 . The choice of the technique seems to depend on operating time, cost of instrumentation and rate of complication.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have proposed surgical correction (metroplasty) of uterine anomalies related to DES exposure, including T-shaped distortion 49 or simple overall reduction of uterine size. 50 Although authors reporting on small series recount positive impressions about the impact of surgery on subsequent reproductive outcome, 51 the efficacy of these procedures remains to be rigorously evaluated.…”
Section: Anatomy and Morphological Measurementsmentioning
confidence: 99%